High-Speed Adaptive Turbo Decoding Algorithm and Its Implementation - Min Hyuk Kim; Jin-Hee Jeong; Ji-Won Jung (Proceedings of 2006 IEEE Information Theory Workshop (ITW '06) : October 22-26, Chengdu, China, 2006)
In this paper, we propose an adaptive turbo decoding algorithm for high order modulation scheme combined with originally design for a standard rate-1/2 turbo decoder for B/QPSK modulation. A transformation applied to the incoming I-channel and Q-channel symbols allows the use of an off-the-shelf B/QPSK turbo decoder without any modifications. .The source of the latency and power consumption reduction is from the combination of the radix-4, dual-path processing, parallel decoding, and early-stop algorithms. We implemented the proposed scheme on a field-programmable gate array (FPGA) and compared its decoding speed with that of a conventional decoder